Code-Switching in Russian by Old Believers in Latgale (Latvia) - ПилиПенко, Глеб Петрович (Jezikoslovni zapiski, 2018)
This article presents code-switching strategies in Russian among Old Believers in Latgale (Latvia). This phenomenon is not very widespread in the corpus of spoken texts that was collected during field research in 2016. The most often registered case of code-switching occurs when quoting other speakers or one’s own speech in Latvian. Various linguistic and pragmatic strategies appear in such quotations. Code-switching is linked with speakers’ identity. The article compares code-switching in the language of Old Believers in Latgale with code-switching among Slovenians living in the Trieste area.